2019
DOI: 10.7150/thno.27550
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived extracellular vesicles inhibit osteogenesis and exacerbate myeloma bone disease

Abstract: Background: As a hallmark driver of multiple myeloma (MM), MM bone disease (MBD) is unique in that it is characterized by severely impaired osteoblast activity resulting from blocked osteogenesis in bone marrow-derived mesenchymal stem cells (BM-MSCs). The mechanisms underlying this preferential blockade are incompletely understood.Methods: miRNA expression of MM cell-derived extracellular vesicles (MM-EVs) was detected by RNA sequencing. MM-EVs impaired osteogenesis and exacerbated MBD were in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 56 publications
2
61
0
Order By: Relevance
“…Multiple lines of evidence define the involvement of EVs in MM progression as they can act on several cellular targets and at different levels of disease progression [12][13][14][15][16][17][18][19]. In particular, recent findings have highlighted the role of EVs as inducers of MM-osteolytic bone disease [21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple lines of evidence define the involvement of EVs in MM progression as they can act on several cellular targets and at different levels of disease progression [12][13][14][15][16][17][18][19]. In particular, recent findings have highlighted the role of EVs as inducers of MM-osteolytic bone disease [21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…EVs released by MM cells have been recently correlated to the MM bone disease by directly activating osteoclast functions and, at the same time, by inhibiting the osteogenic differentiation of hMSCs [21][22][23][24][25]27]. In our previous study, we demonstrated that MM EVs inhibit the osteoblastic differentiation of hTERT-MSCs [21]; here we tried to shed light on the mechanism underlying these effects.…”
Section: Evs Are Internalized By Hmscs and Inhibit Their Osteogenimentioning
confidence: 95%
See 1 more Smart Citation
“…Piwi-interacting RNAs (piRNAs) are 21 to 35 nucleotides segments of RNA that can orginate from lncRNAs and are active during development [27]. These are also found in extracellular vesicles (EV), including those from multiple meloma bone disease that are capable of inhibiting osteogenesis [28].…”
Section: Osteogenesis: Cell Proliferation and Differentiationmentioning
confidence: 99%
“…Then, when the cultured cell fusion degree reached between 60% and 70%, the cells were carefully sucked out in order the complete the culture medium, and 2 ml of osteogenic differentiation culture medium were added. The induced differentiation was stained on the 21st day [19,20] .…”
Section: Msc Differentiationsmentioning
confidence: 99%